The impact of aggregate and disaggregate consumption shocks on the Equity Risk Premium in the United Kingdom - Poshakwale, Sunil S.; Chandorkar, Pankaj (Peking University Press, 2019)
We examine the impact of aggregate and disaggregate consumption shocks on the ex-post Equity Risk Premium (ERP) of FTSE indices and the 25 Fama-French portfolios. Findings suggest that aggregate consumption shocks seem to explain significant time variation in the ERP. At disaggregated level, the ERP increases when the actual consumption is less than expected. Finally, durable and semi-durable consumption shocks have a greater impact on the ERP than non-durable consumption shocks
Keywords: Equity Risk Premium; Consumption Wealth Channel; Consumption Shocks; Structural Vector Autoregression; Asset Pricing